2018
DOI: 10.1369/0022155418766515
|View full text |Cite
|
Sign up to set email alerts
|

Potential Value of YAP Staining in Rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is a common malignancy of soft tissue, subclassified as alveolar (ARMS), pleomorphic (PRMS), spindle cell/sclerosing (SRMS), and embryonal (ERMS) types. The Yes-associated protein (YAP) is a member of the Hippo pathway and a transcriptional regulator that controls cell proliferation. We have studied the immunohistochemical expression of YAP in different RMSs, arranged in tissue microarray (TMA) and whole slide formats. Pertinent clinical data including patient age, gender, tumor location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…An increased expression of YAP has been described in many human adult and pediatric cancers, and its expression is associated with an advanced clinical stage and short overall survival in different tumors [ 28 ]. Several studies have revealed that nuclear YAP is more prevalent in ERMS and SRMS than in ARMS, even if its role in RMS has not been clarified yet [ 29 , 30 ]. Furthermore, at a transcriptional level, S-RMS1 showed a higher level of the neovascularization markers endoglin [ 22 ] and GATA-6 [ 31 ] while TGFβ1R was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…An increased expression of YAP has been described in many human adult and pediatric cancers, and its expression is associated with an advanced clinical stage and short overall survival in different tumors [ 28 ]. Several studies have revealed that nuclear YAP is more prevalent in ERMS and SRMS than in ARMS, even if its role in RMS has not been clarified yet [ 29 , 30 ]. Furthermore, at a transcriptional level, S-RMS1 showed a higher level of the neovascularization markers endoglin [ 22 ] and GATA-6 [ 31 ] while TGFβ1R was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…3 Yes-associated protein (YAP) is associated with sarcoma genesis in RMS patients and is more prevalent in ERMS than ARMS, thus differentiating the two. 13 The differential diagnosis of orbital RMS includes proptosis secondary to inflammatory, infectious, vascular, and neoplastic conditions, and thus careful histological examination is required to differentiate such lesions. 14 In our case, the marked pleomorphism noted was critical for differentiating RMS from Ewing's sarcoma.…”
Section: Discussionmentioning
confidence: 99%